The Latest Trends in the Global Luxury Fashion Market – The Case of Russia - Shuvatov, Nikita; De Castro, Tereza; Kováčiková, Viera; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
It has been noted over the years that the world luxury market has been steadily growing despite turbulence in other market categories, and Russia has established itself as one of the most promising developing markets in the field of luxury goods, with a significant increase in the size of the luxury goods market in recent years. This thesis assesses the evolution of the luxury market, including a more in-depth examination of the concept of luxury, customer perception and value creation of items of luxury, and current industry trends. The main objective of the thesis is to assess the trends in the global fashion luxury market, with a particular emphasis on recent developments and the unique specifics of the Russian luxury market. Results of the research reveal that the aims of Western fashion luxury companies differed in the Russian market with a great emphasis on attracting the Russian consumers to spend more domestically, while sustainability was promoted elsewhere in the world. The demand for the luxury goods did not decrease with the withdrawal of Western luxury companies and consumers are still finding a way to access luxury goods, mainly through retailers and neighbouring countries.
Vedoucí práce: Tereza De Castro
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses